Direct structure determination of a composite double-layer surface alloy by x-ray photoelectron diffraction: p (2×2)-Na/Al(111) - Fasel, Roman; Aebi, Philipp; Schlapbach, Louis; Osterwalder, Jürg (My University, 1995)
The local structure of p(2×2)-Na/Al(111) has been investigated using angle-scanned full hemispherical x-ray photoelectron diffraction. The resulting diffraction patterns allow a direct and unequivocal determination of the surface atomic structure. Even though Na and Al are completely immiscible in the bulk, the p(2×2)-Na/Al(111) phase consists of a composite double-layer surface alloy where Na atoms take substitutional and fcc hollow sites and Al atoms removed from the surface occupy hcp hollow sites.